O sagrado feminino e a serpente: performance mítica na simbologia das danças circulares sagradas - Bonetti, Maria Cristina de Freitas (2013)
This thesis investigates the survival and the camouflage of the Myth of the Serpent and the Cult to the Great Mother in mythic and ritualistic performances of the Sacred Circle Dances nowadays. For this, it remakes the myth trajectory since ancient times, exploring the imagery of creation and its various expressions in archaic cultures in the Western World. The main objective of the research is to demonstrate the survival the symbolism of the Mother Goddess and the Serpent Myth in different cultural expressions in dialogue with the Sacred Circle Dances. It also takes into to identify the hidden message that externalizes through body movements that generate archetypical expressions codified in the ritualistic dances and performances, and explores in the same way, the domains of the Great Mother and the Serpent; its symbolic polysemy and the way they are organized in artistic and spacial terms. The main issue of this thesis is that whether the symbolism of the serpent can be considered as a mythical theme survival in the contemporary Sacred Circle Dance. Taking as methodological inspiration the hermeneutic conception of analysis, in this thesis the purpose is to connect the Myth of the Serpent with the most relevant works regarding the Sacred Feminine, history, anthropology and the ritualistic performances. The literature will be reviewed in its thematic axles and in particular the authors and the known experts in the Sciences of Religion. Amid the conceptual interpretations this research produces surveys of recent works on the subject of study to discuss the meanings and the ramifications inspired by ancient traditions and with deep power refresher mythical; and in this discussion, focuses on the aspect of the dances that revive the serpent symbolism and ritually reframe the archaic myths. Traditional and Folk Dances, realized as artistic performances, or even spontaneously, come upon the space created by the traditional parties, replace and vivify myths and prehistoric rituals nowadays. It is considered, therefore, that the Serpent symbology is a mythical theme of the Mother Goddess who survived the performed and ritualistic acts in the contemporary Sacred Circle Dances.